2019
DOI: 10.3390/min9110695
|View full text |Cite
|
Sign up to set email alerts
|

Apatite from NWA 10153 and NWA 10645—The Key to Deciphering Magmatic and Fluid Evolution History in Nakhlites

Abstract: Apatites from Martian nakhlites NWA 10153 and NWA 10645 were used to obtain insight into their crystallization environment and the subsequent postcrystallization evolution path. The research results acquired using multi-tool analyses show distinctive transformation processes that were not fully completed. The crystallization history of three apatite generations (OH-bearing, Cl-rich fluorapatite as well as OH-poor, F-rich chlorapatite and fluorapatite) were reconstructed using transmission electron microscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Similarly, other elemental maps show elemental presence only in the region where the minerals which have these elements are present. As Raman spectroscopy can detect differences in mineral structure 42 , 46 and crystalline orientation 41 , it was possible to distinguish biotite-1 and biotite-2 from one another, whereas with EDS such a distinction was not possible. Specifically, while the composite EDS and Raman maps show an overall good correlation in terms of the type and location of minerals, polymorphs of biotite can only be distinguished by Raman imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, other elemental maps show elemental presence only in the region where the minerals which have these elements are present. As Raman spectroscopy can detect differences in mineral structure 42 , 46 and crystalline orientation 41 , it was possible to distinguish biotite-1 and biotite-2 from one another, whereas with EDS such a distinction was not possible. Specifically, while the composite EDS and Raman maps show an overall good correlation in terms of the type and location of minerals, polymorphs of biotite can only be distinguished by Raman imaging.…”
Section: Resultsmentioning
confidence: 99%
“…However, given that the nakhlites are the least shocked martian meteorites (~15-20 GPa; e.g., Malavergne et al, 2001;Treiman and Irving, 2008), the effects of shock on apatite and other minerals are considered minimal, and apatite in the nakhlites represent a good starting point to observe structures related to their petrogenetic formation processes. More recently, the first studies on the microstructure of extraterrestrial apatite (i.e., Słaby et al, 2017;Birski et al, 2019) have demonstrated that microand nanostructural examination of apatite has the potential to provide constraints on conditions of crystallization, precipitation, and fluid interaction of a magmatic source. Furthermore, the volatile contents and isotopic compositions (D/H (deuterium/hydrogen), 37 Cl/ 35 Cl, 18 O/ 16 O) in apatite have been used to better understand many of these processes related to the origin and evolution of Mars (e.g., Williams et al, 2016;Shearer et al, 2018;Peslier et al, 2019;Barnes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, these technologies have been successfully employed for detailed investigations of new minerals in both meteorites and terrestrial rocks, especially when their synthetic analogs are well known. During 2018-2020, 15 phases recently found in meteorites were approved by the Commission on New Minerals, Nomenclature and Classification (CNMNC) of the International Mineralogical Association (IMA) as new mineral species [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] [11,[25][26][27][28]. Of course, these few works cannot cover all mineral-forming processes occurring in meteorites.…”
mentioning
confidence: 99%
“…Of course, these few works cannot cover all mineral-forming processes occurring in meteorites. In general, the articles presented include local studies of particular meteorites and their mineralogy by advanced analytical techniques [25,26], refinement of crystal structure for the rare phosphate (xenophyllite) [27], and description of new meteorite minerals and mineral associations [11,28].…”
mentioning
confidence: 99%
See 1 more Smart Citation